Vitamin E levels in buccal cells of arsenicosis patients following vitamin E supplementation - Mir Misbahuddin; Nadia Farha (Bangladesh Pharmacological Society, 2013)
To understand the role of vitamin E in the treatment of arsenical melanosis and keratosis, the buccal cells of 19 patients, 14 arsenic exposed controls and 13 healthy volunteers were collected for the estimation of vitamin E both before and after supplementation with vitamin E (200 IU, caplet) daily orally for 20 weeks. The vitamin E levels in the buccal cells of patients were significantly low in comparison to healthy volunteers (healthy vs patients: 17.2  ±  4.4 vs 12.3 ± 6.1 mg/mg of protein; p=0.012). These low level of vitamin E in patients returned toward normal levels following supplementation with vitamin E for 20 weeks (p=0.044). The vitamin E levels in serum of patients were also low (healthy vs patients: 18.9 ± 4.4 vs 10.2 ± 2.6  mg/mL; p=0.000). Supplementation with vitamin E overcomed the low levels of vitamin E in serum. The cholesterol levels in buccal cells and serum of patients were significantly low in comparison to healthy volunteers (buccal cells of healthy vs patients: 24.5 ± 14.1 vs 10.3 ± 9.8 mg/mg of protein; p=0.005; serum of healthy vs patients: 153.5 ± 22.8 vs 125.3 ± 37.0 mg/dL; p=0.012). After supplementation of vitamin E, there was no significant change in cholesterol levels in both buccal cells and serum of patients.